2018
DOI: 10.1007/s12471-018-1214-1
|View full text |Cite
|
Sign up to set email alerts
|

Differences at surgery between patients with bicuspid and tricuspid aortic valves

Abstract: AimTo determine differences in surgical procedures and clinical characteristics at the time of surgery between native bicuspid aortic valves (BAV) and tricuspid aortic valves (TAV) in patients being followed up after aortic valve surgery (AVS).MethodsIn this retrospective cohort study in a non-academic hospital, we identified patients who had a surgeon’s report of the number of native valve cusps and were still being followed up. We selected patients with BAV and TAV, and used multivariable regression analyses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…The relationship of CAD and the aortic valve morphology and a possible atheroprotective effect of BAV is a topic of ongoing debate. [5][6][7][8] Previous studies have shown a significantly larger aortic valve calcium volume in BAV patients than TAV patients, 5 but strikingly a lower prevalence of cardiovascular risk factors, coronary calcification, CAD and coronary revascularisation. 3 6-8 These observations imply that the aortic valve calcifications in BAV disease merely reflect local degenerative changes rather than systemic atherosclerotic changes.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship of CAD and the aortic valve morphology and a possible atheroprotective effect of BAV is a topic of ongoing debate. [5][6][7][8] Previous studies have shown a significantly larger aortic valve calcium volume in BAV patients than TAV patients, 5 but strikingly a lower prevalence of cardiovascular risk factors, coronary calcification, CAD and coronary revascularisation. 3 6-8 These observations imply that the aortic valve calcifications in BAV disease merely reflect local degenerative changes rather than systemic atherosclerotic changes.…”
Section: Discussionmentioning
confidence: 99%
“…BAV may be present in up to 30% of patients undergoing SAVR. 32 Bicuspid aortic valve anatomy, larger annular size, bulky and asymmetric leaflet calcification and dilated ascending aorta all pose technical challenges to TAVI which are not prohibitive risk factors for surgery. In fact, associated pathology of aneurysms of the aortic root and ascending aorta can be treated at the time of SAVR with little additional risk.…”
Section: Discussionmentioning
confidence: 99%
“…Thirty-five studies 7,12,13,[17][18][19][20][21][22][23][24][25][26]28,29,[31][32][33][34]36,39,40,[45][46][47][48][49][50][51]53,[55][56][57][58][59]…”
Section: Diabetes Mellitusmentioning
confidence: 99%